The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1021/bi00256a003
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of isolectins of wheat germ agglutinin for sialyloligosaccharides: a 360-MHz proton NMR binding study

Abstract: The binding of three purified sialic acid containing oligosaccharides to two isolectins of wheat germ agglutinin (WGA I and WGA II) has been quantitated by measuring the broadening of a ligand resonance in the proton nuclear magnetic resonance (1H NMR) spectrum at 360 MHz. The ligands, isolated from bovine colostrum by using the procedure of Schneir and Rafelson [Schneir, M. L., & Rafelson, M. E., Jr. (1966) Biochim. Biophys, Acta 130, 1--11], were identified by 1H NMR as the alpha (2,3) and alpha (2,6) isomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

1989
1989
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 37 publications
5
53
0
Order By: Relevance
“…This rationale would also explain the difference between binding scores of sites Blcz and C2,, in the WGAI/T5 complex (1,273 versus 1,346), where the u2,3-linked NeuNAc sits in site C2,,, and the a2.6 linked NeuNAc in site Blcr. AIthough these discrepancies are within what we believe to be the uncertainty of HINT data, they agree with earlier binding data (Kronis & Carver, 1982), and with the NeuLac/WGAI crystal structure revealing that stronger binding of a2,3-NeuLac is due to additional contacts involving Tyr 66 (Wright, 1990).…”
Section: Neunac Bindingsupporting
confidence: 90%
“…This rationale would also explain the difference between binding scores of sites Blcz and C2,, in the WGAI/T5 complex (1,273 versus 1,346), where the u2,3-linked NeuNAc sits in site C2,,, and the a2.6 linked NeuNAc in site Blcr. AIthough these discrepancies are within what we believe to be the uncertainty of HINT data, they agree with earlier binding data (Kronis & Carver, 1982), and with the NeuLac/WGAI crystal structure revealing that stronger binding of a2,3-NeuLac is due to additional contacts involving Tyr 66 (Wright, 1990).…”
Section: Neunac Bindingsupporting
confidence: 90%
“…Further blotting studies and subsequent use of WGA agglutinin as a probe revealed that a glycoprotein S14 with an apparent molecular mass of 14 kDa was dominant among the released proteins. The specificity of this plant lectin had been attributed to the sugar moieties NeuNAc as well as GlcNAc (Kronis and Carver, 1982). Glycoproteins comprising those sugar residues occur frequently, from plants to metazoa (Karpati et al, 1999).…”
Section: Discussionmentioning
confidence: 96%
“…We can therefore conclude that a K d ϳ 30 M reflects the binding affinity of the lectin domain for ␣-Neu5Ac, which is a relatively high affinity for carbohydrate recognition. Wheat germ agglutinin (2CWG) has a K d ϳ 100 M with sialyllactose (40), but this also involves contributions from interactions of the galactose. Influenza virus hemagglutinin (5HMG) has a K d ϳ 1 mM with sialyllactose (41), as does the VP4 sialic acid binding domain of the rhesus rotavirus (1KQR) (34).…”
Section: Std Nmr Experiments To Investigate the Binding Of Neu59ac 2mentioning
confidence: 99%